The impact of personality on participation decisions in surveys : A contribution to the discussion on Unit Nonresponse - Sabenroth, Denise (Springer Fachmedien Wiesbaden, 2013)
Increasing nonresponse rates in surveys are a matter of concern internationally, as low response rates put the quality of survey data into question. The risk of biased data is high if nonrespondents differ significantly from respondents. In arguing that sample persons' personality traits are decisive in survey participation decisions, Denise Saßenroth investigates the mechanisms causing increasing nonresponse rates. Based on a modification of the Social Isolation Hypothesis, she analyses the impact of sample persons' personality on participation decisions with data from the German General Social Survey and the LISS Panel from the Netherlands.   Contents ·         Survey Nonresponse ·         Sample Persons' Personality and Survey Refusals ·         Personality Effects on Participation in the GGSS (ALLBUS) ·         Personality Effects on Participation in the LISS Panel   Target Groups ·         Researchers and students in the field of the social sciences ·         Survey practitioners   Author Dr. Denise Saßenroth is a social scientist and research associate at the German Institute for Economic Research (DIW Berlin).